FAKTOR-FAKTOR YANG MEMPENGARUHI PENAMBATAN NITROGEN OLEH MIKROORGANISME NON SISBIOTIK - Nana Danapriatna (PARADIGMA : JURNAL ILMU PENGETAHUAN AGAMA, DAN BUDAYA, 2003)
The forms of nitrogen can use by plant are nitrate and amonia, but in the world content of them are limited. Form of nitrogen which big content in the world is dinitrogen (N,), this form is not use by plant without transformation to be N03‘ or NH/ . To be use dinitrogen is needed action of fixing nitrogen microorganism or fertilizers fabrications. The nitrogen fixing proccss by microorganism was influenced by ecological factor, adequate of nutrition and energy, and genetic of microorganism it self. The ecological factor which influenced of nitrogen fixing by microorganism are N;. CO,, O,, RH, pH, temperature, and existing other microorganism. Energy and nutrition which needed by fixing microorganism are C-organic, Mo. Co, Fc, P, Ca. Na, and several of vitamins.